Do feelings explain the choices of voters? - Oliveira, Adriano (2016)
The central hypothesis of this article is that voters have feelings for candidates who motivate their choices. This article aims to prove the hypothesis presented. Longing, excitement and fear are the feelings of the covered suffragettes, which were extracted from various opinion polls conducted in the state of Pernambuco during the presidential election of 2014. To test the hypothesis suggested, we use descriptive statistics and statistical models. Studies on the feelings of voters are scarce in Brazilian scientific production. This article seeks to fill this gap and to encourage further work on feelings of voters.